Manufacturing standards of performance for success - Sweeney, Mike T.; Szwejczewski, Marek (Cranfield School of Management, 1995)
This paper details the findings of a study of the manufacturing performances and practices of 140 engineering companies in the UK. From this study, significant differences in the manufacturing competitiveness of these firms have been identified. Causes for the performance differences are discussed and recommendations are made for the design of a manufacturing strategy to improve manufacturing competitiveness.